Simulation of a downdraft gasifier for production of syngas from different biomass feedstocks - Paiva, Mateus Vinicius (2021)
In the evaluation of gasification processes, estimating the composition of the fuel gas for different conditions is fundamental to identify the best operating conditions. In this way, modeling and simulation of gasification provide an analysis of the process performance, allowing for resource and time savings in pilot-scale process operation, as it predicts the behavior and analyzes the effects of different variables on the process. Thus, the focus of this work was the modeling and simulation of biomass gasification processes using the UniSim Design chemical process software, in order to satisfactorily reproduce the operation behavior of a downdraft gasifier. The study was performed for two residual biomasses (forest and agricultural) in order to predict the produced syngas composition. The reactors simulated gasification by minimizing the free energy of Gibbs. The main operating parameters considered were the equivalence ratio (ER), steam to biomass ratio (SBR), and gasification temperature (independent variables). In the simulations, a sensitivity analysis was carried out, where the effects of these parameters on the composition of syngas, flow of syngas, and heating value (dependent variables) were studied, in order to maximize these three variables in the process with the choice of the best parameters of operation. The model is able to predict the performance of the gasifier and it is qualified to analyze the behavior of the independent parameters in the gasification results. With a temperature between 850 and 950 C, SBR up to 0.2, and ER between 0.3 and 0.5, the best operating conditions are obtained for maximizing the composition of the syngas in CO and H2.